NUMBER OF CASES OF VARICELLA AND HOSPITALIZATION IN A PEDIATRIC REFERENCE HOSPITAL IN BRAZIL AFTER INTRODUCING THE VACCINE - Pinto,Isabella Cristina Tristão (2021)
ABSTRACT Objective: To assess the number of cases and the profile of hospitalizations from varicella after the introduction of the measles, mumps, rubella and varicella combination vaccine in the public health system. Methods: Retrospective study in an infectious diseases pediatric hospital of reference in Southeast Brazil. The cases with a clinical diagnosis of varicella, from January 2011 to June 2016, were assessed from pediatricians’ medical records. The hospitalizations were classified into a pre-vaccine group and post-vaccine group, based on the date the vaccine was introduced (September 2013). Both groups were compared by age, sex, time of hospitalization, reason for hospitalization, hospital complications, duration of intensive care, and clinical outcome. Results: A total of 830 hospitalizations were recorded; 543 in the pre-vaccine period and 287 in the post-vaccine period, a reduction of 47.1% (p<0.001). In both periods, a similar profile in the hospitalizations was noticed: majority male; aged between one to five years old; most complications due to secondary causes (mainly skin infections); main outcome was clinical improvement and discharge from the hospital. In the pre-vaccine period, six deaths were recorded and two were recorded in the post-vaccine period. Conclusions: The profile of the hospitalizations was expected to stay the same since this study did not compare vaccinated with unvaccinated children, but hospitalizations before and after the vaccine was introduced. In accordance with the medical literature, we found a significant fall in the number of hospitalizations from varicella.